Dançando com os Orixás - Bahia, Joana (2014)
The presence of Brazilians in Europe has been expressive since the socioeconomic changes which occurred in the international context. Nowadays, this migration developed in North Europe. In Germany, 216.285 migrants come from Latin America, 31.918 are Brazilians. We consider in this article the importance of the so called "african dance" in afro Brazilians religions and how the artistic performance leads to a ritual performance. It means how the mains shamans that expand the religion are related to the afro Brazilian dance and music scene. Our work analyses the annual presence of afoxé (cultural and artistic groups based in the afro Brazilian doctrines) in the Carnival of Cultures in Berlin. Its shows the importance of the afro-Brazilian religions in recreating an idea of "Africa" in Europe. Our field work also took place in the Ilê Obá Silekê and Forum Brasil, both located in Berlin and coordinated by pai de santo (Shaman) Murah. He is very well known as a Afro Brazilian dancer all over the country for 20 years. They are assisted by Germans, Brazilians and other nationalities as Americans and Italians. The candomblê is one of the most important parts of a kind of little Brazil in Berlin. The participants of candomblê are also dancers, musicians, artists who participate in the cultural activities promoted in the city as a whole. We consider how these ethnic brokers are important to circulate important ethnic symbols, specially the so called afro Brazilian religion symbols.